South East European International Institute for Sustainable Technologies (SEEIIST) - Amaldi, Ugo; Benedetto, Elena; Damjanovic, Sanja; Dosanjh, Manjit; Durante, Marco; Georgieva, Petya; Haberer, Thomas; Plesko, Mark; Ristova, Mimoza; Rossi, Sandro; Sammut, Nicholas; Sapinski, Mariusz; et al. (Frontiers in Physics, 2021)
The South East European International Institute for Sustainable Technologies (SEEIIST) was proposed in 2016 at the World Academy of Art and Science, with the objective of building a facility for charged particle cancer therapy for the South Eastern European countries. SEEIIST will offer the world-class research needed to reduce or even revert the brain drain that is causing a shortage of talent and economic losses in South East Europe. There is no particle therapy in South-East Europe in spite of a growing number of cancers being diagnosed. The facility beam time will be shared 50:50 between treating patients and performing research with a wide spectrum of different light ions beyond the presently used protons and carbon ions, which will make the facility unique in the world. The SEEIIST Project is presently in a Conceptual to a Design Phase, implemented with the support of the EU and the involvement of CERN and GSI. The next phase of the project realization will include a final technical design for the facility, a structure and a business plan for the organization and the definition of conditions for the site selection.